Unconventional Crystal Structure of the High-Pressure Superconductor La3Ni2 O7 - Puphal, P.; Reiss, P.; Enderlein, Niklas; Wu, Y. M.; Khaliullin, G.; Sundaramurthy, V.; Priessnitz, T.; Knauft, M.; Suthar, A.; Richter, L.; Isobe, M.; Van Aken, P. A.; et al. (Physical Review Letters, 2024)
The discovery of high-temperature superconductivity in La3Ni2O7 at pressures above 14 GPa has spurred extensive research efforts. Yet, fundamental aspects of the superconducting phase, including the possibility of a filamentary character, are currently subjects of controversial debates. Conversely, a crystal structure with NiO6 octahedral bilayers stacked along the c-axis direction was consistently posited in initial studies on La3Ni2O7. Here, we reassess this structure in optical floating zone-grown La3Ni2O7 single crystals that show signs of filamentary superconductivity. Employing scanning transmission electron microscopy and single-crystal x-ray diffraction under high pressures, we observe multiple crystallographic phases in these crystals, with the majority phase exhibiting alternating monolayers and trilayers of NiO6 octahedra, signifying a profound deviation from the previously suggested bilayer structure. Using density functional theory, we disentangle the individual contributions of the monolayer and trilayer structural units to the electronic band structure of La3Ni2O7, providing a firm basis for advanced theoretical modeling and future evaluations of the potential of the monolayer-trilayer structure for hosting superconductivity.
CRIS-Team Scopus Importer:2024-10-25